Supply chain management and accessibility to point-of-care testing in resource-limited settings: a systematic scoping review - Kuupiel, Desmond; Bawontuo, Vitalis; Drain, Paul K.; Gwala, Nonjabulo; Mashamba-Thompson, Tivani P. (BMC health services research, 2019)
Background World Health Organization (WHO) has created an essential list of in-vitro diagnostics. Supply chain management (SCM) is said to be the vehicle that ensures that developed point-of-care (POC) tests reach their targeted settings for use. We therefore, mapped evidence on SCM of and accessibility to POC testing (availability and use of POC tests) in low- and middle-income countries (LMICs). Methods We conducted a systematic scoping review using Arksey and O’Malley’s framework as a guide. We searched PubMed; CINAHL; MEDLINE; WEB of Science; Science Direct; and Google Scholar databases for studies that focused on POC diagnostic tests and SCM. The review included studies that were undertaken in 140 countries defined by the World Bank as LMICs published up to August 2017. Two reviewers independently screened the abstracts and full articles against the eligibility criteria. The study used the mixed methods appraisal tool version 2011 to assess the risk of bias for the included studies. NVivo version 11 was employed to extract themes from all included studies and results presented using a narrative approach. Results Of 292 studies identified in this review, only 15 published between 2009 and 2017 included evidence on POC diagnostics and SCM. Of the 15 studies, three were conducted in Zambia, one each in Mozambique, Uganda, Guatemala; South Africa, one in Burkina Faso, Zimbabwe, and one multi-country study (Tanzania, Uganda, China, Peru and Zambia and Brazil). Six studies were not country specific since they were not primary studies. Majority of the studies reported stock-outs of HIV, syphilis, and malaria POC tests. There was a moderate to substantial level of agreement between the reviewers’ responses at full article screening stage (Kappa statistic = 0.80, p < 0.01). Nine studies underwent methodological quality appraisal and all, scored between 90 and 100%. Conclusions The results demonstrated limited published research on SCM of and accessibility to POC testing in LMICs. Further studies aimed at investigating SCM of POC tests in resource-limited settings to identify the barriers/challenges and provide a context-specific evidence-based solutions for policy/decision makers, implementers, and POC developers, funders, and development partners would be essential. PROSPERO registration number CRD42016043711.